ANALISIS KONFLIK SOSIAL DALAM CERPEN “CINTA LELAKI BIASA (Asma Nadia - True Story)” - Gita Widia Pardosi; Achmad Yuhdi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
A conflict is an argument or disagreement between two or more people. Political conflicts arose from the existence of political power. The essence of political power is society as an object. Conflict is part of social life and arises from personality differences arising from human interactions. The social conflict in this (Asma Nadia - true story) short story "cinta lelakibiasa" refers to external conflicts, especially social conflicts. This conflict initially arises due to the social status and social class conflict between the wealthy Nania and the poor Lafri. Nania's parents do not bless Rafli to live with Nania because because of this status Nania and Rafli's love becomes an obstacle. This study uses a qualitative descriptive method. Information is provided in the form of words and quotes